Steroid pretreatment of deceased donors and liver allograft function - Ten years follow-up of a blinded randomized placebo controlled trial. (October 2021) - Györi, Georg P.; Mathe, Zoltan; Jelencsics, Kira; Geroldinger, Angelika; Gerlei, Zsuzsanna; Berlakovich, Gabriela A.
Abstract: Background: Within the last decade numerous attempts have been reported in order to expand the donor pool and alleviate organ shortage in the setting of liver transplantation. Aim of this blinded randomized controlled trial was to evaluate the effect of donor steroid pretreatment on outcomes after liver transplantation. Methods: We performed an international, multi-center double-blinded randomized placebo controlled trial. Donors received 1000 mg methylprednisone or placebo before organ procurement. Primary endpoint were patient and graft survival. Secondary end points were rate of BPAR and liver functions trajectories after transplantation. Follow up was 10 years. Results: There was no effect of steroid pretreatment vs. placebo on overall patient survival (50% vs. 46%, p = n.s.) as well as graft survival (47% vs. 51%, p= n.s.). Further donor steroid pretreatment did not alter the rate of biopsy proven acute rejections (34% steroid group vs. 36% placebo, p = n.s.). Evaluating short term and long term graft function, steroid pretreatment had minor effect on immediate liver function trajectories within the first 2 weeks after transplantation. This was not seen in long-term follow up. Conclusion: In conclusion we found no evidence that donor steroid pretreatment translates in improved outcomes after liver transplantation. Highlights: Shortage in donor organs requires constant effort in expanding the donor pool. Targeted donor therapy is one option aiming at improved transplant outcomes. Steroid pretreatment does improve immediate graft function but not longterm outcome.